Maturity Assessment of Critical Technologies - Daiane Rocha; Gisele Lemes Veiga Araujo; Francisco Cristovão Lourenço Melo (Foresight and STI Governance, 2022)
A maturity assessment of technological projects is becoming an increasingly popular tool for innovation policy. It enables the accurate determining of risks and opportunities related to the creation of high-tech products. Determining the degree of technology readiness, especially at early stages of development, increases the performance of not only government programs, but also of business projects. This article presents a software interface for such expertise, the IAE/ITA TRL Calculator, designed for the Brazilian aerospace sector. The validation within a number of cases revealed its potential applicability in a wide variety of industries. This innovative software product includes a quality user guide and an improved visual interface that allows for easy and quick identification of issues that require additional effort in order to move the evaluated technology project to a higher level of readiness.